2000
DOI: 10.1200/jco.2000.18.19.3390
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Comparative Study of High-Dose Cisplatin Versus a Combination of Paclitaxel and Cisplatin in Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: This large randomized phase III trial failed to show a significant improvement in survival for the paclitaxel/cisplatin combination compared with high-dose cisplatin in patients with advanced NSCLC. However, the paclitaxel/cisplatin combination did produce a better clinical response, resulting in an increased time to progression while providing a similar QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
86
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(91 citation statements)
references
References 33 publications
2
86
0
3
Order By: Relevance
“…Interestingly, in a paper reviewing the challenges of novel agents for the design of phase II trials and suggesting early progression as a surrogate endpoint to accept or reject new drugs, a 30% maximum PD rate was identified, above which the agent would have been rejected from further evaluation [79]. In a randomized trial of high-dose cisplatin versus cisplatin plus paclitaxel, the addition of the taxane resulted in a 9% higher ORR, whereas the risk for progression was 13% lower, with no significant difference in OS [80]. In a similar study of gemcitabine-cisplatin compared with cisplatin alone, the ORRs were 30.4% and 11.1%, respectively; the risk for PD was 18% lower and the median survival duration was significantly longer in the gemcitabine arm [10].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a paper reviewing the challenges of novel agents for the design of phase II trials and suggesting early progression as a surrogate endpoint to accept or reject new drugs, a 30% maximum PD rate was identified, above which the agent would have been rejected from further evaluation [79]. In a randomized trial of high-dose cisplatin versus cisplatin plus paclitaxel, the addition of the taxane resulted in a 9% higher ORR, whereas the risk for progression was 13% lower, with no significant difference in OS [80]. In a similar study of gemcitabine-cisplatin compared with cisplatin alone, the ORRs were 30.4% and 11.1%, respectively; the risk for PD was 18% lower and the median survival duration was significantly longer in the gemcitabine arm [10].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the fact that a phase III randomised trial showed better survival with paclitaxel plus cisplatin, when comparing etoposide with cisplatin (Bonomi et al, 2000), many studies have not demonstrated better survival with paclitaxel plus cisplatin or carboplatin, when compared with conventional chemotherapy (Giaccone et al, 1998;Gatzemeier et al, 2000;Raftopoulos et al, 2002). The dosage and schedule of the paclitaxel used varied widely among the different studies and, thus, probably had different therapeutic effects on the patients.…”
mentioning
confidence: 99%
“…Despite use/ realisation of a high dose intensity of both chemotherapeutic drugs, in addition to a lower rate of neutropenia, also certain nonhaematologic toxicities such as arthralgia/myalgia, asthenia and gastrointestinal symptoms were less commonly seen when compared to other phase II/III studies of this particular drug combination in other disease entities (McGuire et al, 1996;Rose et al, 1999;Gatzemeier et al, 2000). Similarly, in the advanced gastric cancer trials of Roth et al (2000) and Ridwelski et al …”
Section: Discussionmentioning
confidence: 98%
“…The rationale for their combined use were: (1) the documented activity of both drugs in gastric cancer when used as single agent (Wils, 1996); (2) the apparent synergistic efficacy and safety of this combination in patients with ovarian-, head and neck cancer, and NSCLC (Ilson et al, 1998;Gatzemeier et al, 2000;Khuri et al, 2000;Pfisterer, 2000); (3) as well as the encouraging results of two recently published reports of a combination of cisplatin and the semisynthetic taxoid docetaxel (Roth et al, 2000;Ridwelski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation